The new global determinants of FDI flows to developing countries: The importance of ICT and democratization - Tony Addison; Almas Heshmati (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Foreign direct investment (FDI) has increased dramatically in recent years. However, the distribution of FDI is highly unequal and very poor countries face major difficulties in attracting foreign investors. This paper investigates the determinants of FDI inflows to developing countries, with a particular emphasis on the impact of the `third wave of democratization' that started in the early 1980s and the spread of information and communication technology (ICT) that began in the late 1980s. These two global developments must now be taken into account in any explanation of what determines FDI flows. Using a large sample of countries, together with panel data techniques, the paper explores the determinants of FDI. The causal relationship between FDI, GDP growth, trade openness and ICT is investigated. The main findings are that democratization and ICT increase FDI inflows to developing countries. The paper concludes that more assistance should be given to poorer countries to help them to adopt ICT and to break out of their present `low ICT equilibrium' trap.
Keywords: O0; O3; C23; 330; foreign direct investment; ICT; democracy; panel data; Direktinvestition; Informationstechnik; Entwicklungsländer; Demokratisierung